Do we follow the money? The drivers of migration across regions in the EU - Andrés Rodríguez-Pose; Tobias Ketterer; David Castells-Quintana (REGION, 2015)
Most immigration theories tend to highlight that migration follows wealth and economic dynamism, but is this also the case across regions in Europe? The aim of the paper is to investigate whether migrants in Europe indeed follow the money and to contrast this with a variety of potential alternative explanations, including the presence of migrants from a similar origin. The analysis is based on panel data estimations including 133 European regions over a time period of 17 years. Different lag structures have been employed in order to distinguish between short- and long-run effects. The results cast some doubt about the prominence of pecuniary factors as a determinant of cross regional migration in Europe, with little evidence to support the idea that migration follows economic dynamism. Network effects, human capital related-, and 'territorially embedded' innovation enhancing regional characteristics, by contrast, seem to play a much stronger role than hitherto considered.
Keywords: 330; Inter-regional migration; mobility; regional economic growth; social networks; regions